CLINICAL INSIGHT ON PATTERNS OF CARE AND PROGNOSTIC FACTORS IN ADULT HIGH GRADE GLIOMA: EXPERIENCE FROM A TERTIARY CANCER HOSPITAL FROM EASTERN INDIA - SEN, ANNESHA; MANNA, AMITABHA; MANDAL, BIDYUT; BASU, ABHISHEK (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The Central Nervous System Tumors account for 2.4% of all malignancies in India, but are associated with high mortality in high-grade tumors which result in poor death-adjusted life years. This study focuses on patterns of care and prognostic factors of adult high-grade glioma to explore the unaddressed nuances in treating such patients. Methods: It was a retrospective single institutional study from June 2018 to July 2021 with an age group between 16 to 70 years. All histopathologically or clinicoradiologically proven cases of high-grade (World Health Organization Grades III and IV) gliomas were assessed. Defaulters and recurrent glioma at presentation were excluded from the analysis. Baseline characteristics were analyzed by Chi-square and unpaired t-test, and the Kaplan– Meir test was used for survival analysis. p<0.05 was considered significant. Results: 41 patients were accrued for final analysis with a median follow-up period of 18 months. The most common histology was Astrocytoma, followed by Glioblastoma with a female preponderance. The Frontal and Temporal lobe was the predominant site in the study population. A majority (82%) of the patients underwent maximal safe resection followed by chemoradiation therapy (63.4%). Median progression free survival was 24 months and 8 months for Grades III and IV gliomas, respectively. The median overall survival for Grade IV gliomas was 7 months. Conclusion: Resection status, Grade IV, IDH and 1p19q codeletion status were significant prognostic factors, while intensity modulated radiotherapy showed better dosimetry. More prospective randomized studies with larger sample sizes and longer follow-ups are required for validation and drafting an outcome nomogram.